SEMANTIC ANALYSIS OF PHRASEOLOGICAL UNITS (ON THE EXAMPLE OF ALISHER NAVOI'S POETRY) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article provides a semantic analysis of phraseological units of the Tajik language. Phraseologisms are studied structurally-semantically and methodologically. Alisher Navoi's poetry in Tajik was chosen as the object of the article.